A STUDY OF PARTS OF SPEECH USED IN ONLINE THAI FOOD RECIPES - Kingsakul, Wilaiwan; Dennis, Nutprapha (International Journal of Research -GRANTHAALAYAH, 2016)
This case study aims to study parts of speech used in online Thai food recipes from an online cooking website and to examine which parts of speech are frequently used in an online cooking website. The material in this study was 40 Thai food recipes that are selected and analyzed from one online Thai food recipes website. The instrument was a checklist which determines and categorizes parts of speech as nouns, verbs, adverbs, adjectives, pronouns, conjunctions, prepositions and determiners. The data collections were analyzed with the frequency and percentage. The result of the study shows that nouns are the most common part of speech used in an online recipe writing (59%) while pronouns are the least common part of speech found from the study (0%). In conclusion, the most common part of speech found in recipes writing was the noun, while pronouns are the least common part of speech found from the study. The most important thing, in every sentence uses a noun as a subject, as an object and a modifier.